2014
DOI: 10.4236/ojog.2014.45036
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Scratch-Suction and Implantation Failure

Abstract: Objective: The aim of this trial was to determine whether endometrial scratch-suction caused by insertion tube of (IUCD) with suction improved the probability of pregnancy in the subsequent IVF cycle in patients who had previous failed IVF outcome by removing small polyps and any hazardous materials. Design: Observational prospective cohort experimental study. Setting: Zagazig University Hospital, Obstetrics and Gynecology department. From period between September 2011 till September 2012. Population: 30 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Nossair et al . [ 22 ] used intra uterine contraceptive device (IUCD) insertion tube and infant feeding tube in a prospective cohort study to perform scratch suction in women undergoing repeated IVF/ICSI cycles. Maged et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nossair et al . [ 22 ] used intra uterine contraceptive device (IUCD) insertion tube and infant feeding tube in a prospective cohort study to perform scratch suction in women undergoing repeated IVF/ICSI cycles. Maged et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 20 24 25 26 27 ] Yet, there are many unanswered questions regarding timing of injury and many randomized controlled trials have come up in recent years that demonstrate a significant improvement in implantation rate and clinical pregnancy rate when scratching was done in follicular phase of the same cycle. [ 22 10 11 12 13 ] Performing endometrial scratching in follicular phase of the same cycle instead of luteal phase of previous cycle has two advantages. It is more convenient for the women to undergo scratching after transvaginal ultrasound for folliculometry in the same cycle, thus avoiding the need to come in the cycle before IUI.…”
Section: Discussionmentioning
confidence: 99%
“…Further exploration of this phenomenon in a larger group of patients, indeed showed for the fi rst time, that repeated endometrial biopsy substantially increased the IVF outcome in RIF patients [5]. This favorable effect of endometrial biopsy on IVF outcome, was later demonstrated by other clinical centers, most of which selected RIF patients undergoing IVF for their studies [6][7][8][9][10][11][12][13].…”
mentioning
confidence: 86%
“…Also L-selectin is abundant on cell surface of CD56 bright NKs (19); so inhibiting these NKs as a therapeutic protocol by aspirin needs to be investigated further. The inflammatory response of T-helper-1 cells and T-helper-2 cells are respectively necessary for induction of implantation and pregnancy maintenance (59). Another research showed that in uterine stroma cells of healthy women, level of cytokines such as IL-6,8 and transforming growth factor (TGF)-beta were upper than in women with implantation failure history (6).…”
mentioning
confidence: 99%
“…In addition to the above data about the role of inflammation, recently a new technique under the title of "endometrial scratching" is proposed (62). Due to novelty of this technique there were a few free-access related articles like Nossair et al (59) and Singh et al (63). In this technique, via making a scratch-suction on endometrium, we inflame endometrium (up to 6 mm thickness) to prepare it for implantation (64).…”
mentioning
confidence: 99%